Toll-like receptors and integrins crosstalk - Alhamdan, Fahd; Bayarsaikhan, Ganchimeg; Yuki, Koichi (Frontiers in Immunology, 2024)
Immune system recognizes invading microbes at both pathogen and antigen levels. Toll-like receptors (TLRs) play a key role in the first-line defense against pathogens. Major functions of TLRs include cytokine and chemokine production. TLRs share common downstream signaling pathways with other receptors. The crosstalk revolving around TLRs is rather significant and complex, underscoring the intricate nature of immune system. The profiles of produced cytokines and chemokines via TLRs can be affected by other receptors. Integrins are critical heterodimeric adhesion molecules expressed on many different cells. There are studies describing synergetic or inhibitory interplay between TLRs and integrins. Thus, we reviewed the crosstalk between TLRs and integrins. Understanding the nature of the crosstalk could allow us to modulate TLR functions via integrins.